2012
DOI: 10.1158/1078-0432.ccr-11-1530
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Runx2 and Estradiol on Breast Cancer Cell Proliferation: In Vitro Identification of Reciprocally Regulated Gene Signature Related to Clinical Letrozole Responsiveness

Abstract: Purpose To assess the clinical significance of the interaction between estrogen and Runx2 signaling, previously demonstrated in vitro. Experimental design MCF7/Rx2dox BCa cells were treated with estradiol and/or doxycycline to induce Runx2, and global gene expression was profiled to define genes regulated by estradiol, Runx2, or both. Anchorage-independent growth was assessed by soft agar colony formation assays. Expression of gene-sets defined using the MCF7/Rx2dox system was analyzed in pre- and on-treatme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 48 publications
7
52
0
Order By: Relevance
“…RUNX2 suppresses estrogen activity by decreasing the effect of estradiol on reporter gene expression driven by the estrogen receptor response element [10]. Recent studies on breast cancer cells disclosed that ER-α physically binds RUNX2 and inhibits expression of several RUNX2 target genes, providing a strong antagonistic correlation between the two genes in a different cellular type [22,23]. This opposing effect is verified by our results.…”
Section: Discussionsupporting
confidence: 80%
“…RUNX2 suppresses estrogen activity by decreasing the effect of estradiol on reporter gene expression driven by the estrogen receptor response element [10]. Recent studies on breast cancer cells disclosed that ER-α physically binds RUNX2 and inhibits expression of several RUNX2 target genes, providing a strong antagonistic correlation between the two genes in a different cellular type [22,23]. This opposing effect is verified by our results.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with the involvement of the respective DNA-binding domains in their physical interaction (8, 29), attenuation of the androgen response after RUNX2 induction was associated with decreased recruitment of AR to Type I genes (this study); and, attenuation of the RUNX2 response by androgens was associated with compromised recruitment to its targets (8). In breast cancer cells, a similar relationship of reciprocal attenuation has been documented for most RUNX2- and most estrogen-responsive genes (25, 26). Interestingly, however, RUNX2-stimulated SNAI2 expression in breast cancer cells followed the global trend and was attenuated by estradiol, potentially contributing to the anti-RUNX2 and protective effects that estradiol had with regard to breast cancer cell invasiveness (20).…”
Section: Discussionsupporting
confidence: 57%
“…It has been known that RUNX2 controls genes involved in sterol/steroid metabolism, including Cyp11a1, Cyp39a1, Cyp51, Lss, and Dhcr7, discovered in murine osteoprogenitor cells (Teplyuk et al, 2009). In addition, the tumor suppression property of RUNX2 has been reported in breast cancer cell lines in blocking the effect of estradiol, resulting in inhibiting tumor growth (Chimge et al, 2012). Notably, we found that high expression of RUNX2 in CCA was significantly related with male than female gender.…”
Section: Discussionsupporting
confidence: 49%